Reception of Osip Mandelstam’s Creativity in Interwar Lithuania - Lavrinec, Pavel (Literatūra, 2020)
The presented materials on the reception of Osip Mandelstam’s work were revealed in memoir testimonies, published epistolaries, works on the biography of the writer and scientist Vincas Krėvė and his colleague at the University of Lithuania in Kaunas (Vytautas Magnus University since 1930) Mykolas Banevičius (Mikchail Podshibyakin), and periodicals in Lithuanian and Russian languages. The study showed that among the Lithuanian poets and translators there were connoisseurs of poetry and prose by Mandelstam, but translations into Lithuanian language did not appear during the interwar years. A possible explanation for this is the lack of a demand for this kind of creativity, as the materials of the reception of contemporary Russian literature show. The only text by Mandelstam published in Lithuania in Russian is a translation of the story by Henri Barbusse, reprinted in 1926 by a Kaunas newspaper from a Soviet edition. The only characteristic of his poetry is presented in an article in Russian about the latest Russian poetry, published in 1931 in an academic journal under a pseudonym; its most likely author could be M. Podshibyakin.
Keywords: Osip Mandelstam; Jurgis Baltrušaitis; Henrikas Radauskas; Mykolas Banevičius; 20th century Russian poetry; reception; Lithuanian-Russian literary connections